Stimulating idea generation for new product applications. Issue 4 (3rd December 2018) - Fiorineschi, Lorenzo; Frillici, Francesco Saverio; Gregori, Giovanni; Rotini, Federico
Abstract : Purpose: This paper aims to provide suggestions for the identification of potential new applications for the existing products and/or technologies. Design/methodology/approach: A nine-step method has been developed for extracting information about a product or technology, processing the international patent database (IPD) and extracting useful hints for potential new applications. An academic case study has been used to perform the first application of the proposal. Findings: A novel approach for processing IPD aimed at supporting the identification of new opportunities for exploiting existing products/technologies. The case study application shows that the proposal allows to extract potentially useful and non-obvious suggestions for new product applications. Research limitations/implications: Although some limits inevitably affect this preliminary version of the proposal, important hints for future developments have been inferred for a more comprehensive exploitation of both the firm internal knowledge and the suggestions provided by the international patent database. Practical implications: The achieved results can support firms in expanding market opportunities for their products or technologies. Originality/value: The proposed approach offers a new structured path for stimulating idea generation for new product applications, by exploiting product information and the cooperative patent classification.